2021
DOI: 10.1021/jacs.0c11599
|View full text |Cite
|
Sign up to set email alerts
|

Bright Chromenylium Polymethine Dyes Enable Fast, Four-Color In Vivo Imaging with Shortwave Infrared Detection

Abstract: Optical imaging within the shortwave infrared (SWIR, 1000−2000 nm) region of the electromagnetic spectrum has enabled high-resolution and high-contrast imaging in mice, non-invasively. Polymethine dyes, with their narrow absorption spectra and high absorption coefficients, are optimal probes for fast and multiplexed SWIR imaging. Here, we expand upon the multiplexing capabilities in SWIR imaging by obtaining brighter polymethine dyes with varied excitation wavelengths spaced throughout the near-infrared (700−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 52 publications
0
96
0
Order By: Relevance
“…Thanks to their high quantum yields, when JuloChrom5, Chrom7, JuloFlav7 and ICG were chosen as spectrally distinct fluorophores with preferential excitation at 892, 968, 1065 and 785 nm, respectively, the four‐color experiment was able to be performed at a fast speed about 30 fps, together with the clearly visualized heart and breathing rates (Figure 4c). This work not only opens up opportunities to monitor multiple anatomical and functional parameters simultaneously, but also gives a deeper understanding of how to improve the performance of fluorophores [18a] . Furthermore, Hong et al.…”
Section: Cyanine Fluorophores For Nir‐ii Imaging and Nir‐ii Sensingmentioning
confidence: 94%
See 1 more Smart Citation
“…Thanks to their high quantum yields, when JuloChrom5, Chrom7, JuloFlav7 and ICG were chosen as spectrally distinct fluorophores with preferential excitation at 892, 968, 1065 and 785 nm, respectively, the four‐color experiment was able to be performed at a fast speed about 30 fps, together with the clearly visualized heart and breathing rates (Figure 4c). This work not only opens up opportunities to monitor multiple anatomical and functional parameters simultaneously, but also gives a deeper understanding of how to improve the performance of fluorophores [18a] . Furthermore, Hong et al.…”
Section: Cyanine Fluorophores For Nir‐ii Imaging and Nir‐ii Sensingmentioning
confidence: 94%
“…Recently, Sletten group further found that if the phenyl group at the 2‐position of Flav7 was substituted by a tert‐butyl group, the quantum yield of Flav7 derivative Chrom7 can be enhanced up to 1.7% (Figure 2). [18a] Although such great achievements have they made, the quenching property of Flav7 and its derivatives (including dye IR‐26) under physiological conditions inevitably hamper their applications in vivo. To solve this problem, by shortening the polymethine chain and introducing diethylamino and methoxy groups into the end groups of IR‐26, Zhang group developed a series of anti‐quenching pentamethine cyanine fluorophores BTCs with stable peak absorption/emission up to 1014/1070 nm (Figure 2).…”
Section: Cyanine Fluorophores For Nir‐ii Imaging and Nir‐ii Sensingmentioning
confidence: 99%
“…By coupling with ICG as the third channel, they finally achieved three-color, high-speed and real-time bioimaging ( Figure 1D,E ) ( Cosco et al, 2020 ). With the added companion of chromenylium dyes to flavylium dyes, they performed the four-channel bioimaging (ICG, JuloChrom5, Chrom7 and JuloFlav7) ( Cosco et al, 2021 ).…”
Section: Pharmacokinetics Improvement and In Vivo Imaging Of Nir-ii Cyanine Dyesmentioning
confidence: 99%
“…Besides, recent academic publication has shown that in addition to the length of the polymethine chain, substituents affect the brightness of cyanine dyes (Cosco et al, 2017;Cosco et al, 2020;Lei et al, 2019;Pengshung et al, 2020;Wang et al, 2019). For example, Sletten's group found choosing substituents with fewer vibration modes could significantly increase the fluorescence Tao et al (2013) quantum yield of the dye, which is attributed to the reduction of non-radiative energy dissipation (Cosco et al, 2021).…”
Section: The Enhancement Of Nir-ii Brightnessmentioning
confidence: 99%
“…They have gone through the development process from inorganic to organic materials as well as from polymer macromolecules to small molecules. Inorganic materials have been developed, for example, carbon nanotubes ( Robinson et al, 2012 ; Diao et al, 2015b ; Hong and Dai, 2016 ), quantum dots (QDs) ( Dong et al, 2013 ; Zhu et al, 2013 ; Liu P. et al, 2020 ; Liu H. et al, 2020 ; Yang H. et al, 2021 ), and rare Earth nanoparticles ( Naczynski et al, 2013 ; Villa et al, 2014 ; Kong et al, 2019 ), have been employed as NIR-II fluorophores, and NIR-II organic materials have also been synthesized, such as donor-acceptor (D-A) conjugate polymer or molecule ( Antaris et al, 2016 ; Zhang et al, 2016 ; Jiang et al, 2019 ; Gao et al, 2020 ), cyanine/polymethine/bodipy molecule ( Zhu et al, 2018a ; Shi et al, 2018 ; Lei et al, 2019 ; Godard et al, 2020 ; Bian et al, 2021 ; Cosco et al, 2021 ), and organometallic complex ( Yang et al, 2018 ; Shen et al, 2021 ). Due to the improvement of NIR-II contrast agents and traditional UV-Vis-NIR bioimaging technologies (Fluorescence, Photoacoustic, Fluorescence-Lifetime, etc.…”
Section: Introductionmentioning
confidence: 99%